1989
DOI: 10.1002/bjs.1800761006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 828 servicemen killed or injured by explosion in Northern Ireland 1970–84: The hostile action casualty system

Abstract: Death and injury due to terrorist bombings continue to exercise civilian and military surgeons alike. In this paper 828 servicemen killed and injured by explosions in Northern Ireland have been studied, using data stored in the Hostile Action Casualty System (HACS). Because of the nature of the conflict in Northern Ireland, the magnitude of each explosion and the distance of the victims from it are quite accurately known. The overpressure (blast loading) to which the victim was exposed can be estimated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(59 citation statements)
references
References 4 publications
2
56
0
Order By: Relevance
“…Although civilian studies have reported a higher rate of TM rupture in terrorist bombing victims, a recent review of over 4000 explosion casualties from OEF and OIF found a 9% incidence of TM rupture. Previous studies have reported a wide range of incidences for TM rupture (9%-47%) 21,22 among patients injured by explosion. The incidence of 17% TM rupture in our study is within the range of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although civilian studies have reported a higher rate of TM rupture in terrorist bombing victims, a recent review of over 4000 explosion casualties from OEF and OIF found a 9% incidence of TM rupture. Previous studies have reported a wide range of incidences for TM rupture (9%-47%) 21,22 among patients injured by explosion. The incidence of 17% TM rupture in our study is within the range of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the incidence of blast lung in survivors admitted to hospitals was low (approx. 1 -2%) [8], but higher percentages were reported for explosions in confined spaces (e.g. figures ranging from 63% to 94% of critically injured civilian survivors in the Madrid train bombings [9,10]).…”
Section: Classification Of Blast Injuriesmentioning
confidence: 95%
“…An analysis of military casualties from terrorist bombings [8] found that blast lung was frequently identified at post-mortem examination but, in the majority of cases, that death could also be attributed to other causes such as penetrating wounds, head injuries or traumatic amputations. In general, the incidence of blast lung in survivors admitted to hospitals was low (approx.…”
Section: Classification Of Blast Injuriesmentioning
confidence: 99%
“…Air pressure levels of 5 PSI (pounds/ square inch) cause traumatic perforations in the tympanic membrane. The rate of perforation is 50% at levels of more than 15 PSI and 83%, if the level is between 30 and 50 PSI (244-422 kPa), and in these cases perforations are usually bilateral and the mortality rate increases considerably [9][10][11][12][14][15][16][17][18]. Besides the intensity of pressure, the duration of the exposure is also important.…”
Section: Discussionmentioning
confidence: 99%